Development of a Sterne-Based Complement Fixation Test to Monitor the Humoral Response Induced by Anthrax Vaccines - Adone, Rosanna; Sali, Michela; Francia, Massimiliano; Iatarola, Michela; Donatiello, Adelia; Fasanella, Antonio (Frontiers in Microbiology, 2016)
Anthrax is a zoonotic disease caused by Bacillus anthracis spore-forming bacterium. Since it is primarily a disease of animals, the control in animals and humans depends on the prevention in livestock, principally cattle, sheep and goats. Most veterinary vaccines utilize the toxigenic, uncapsulated (pXO1+/pXO2–) B.anthracis strain 34F2 which affords protection through the production of neutralizing antibodies directed to the toxin components Protective Antigen (PA), Lethal Factor (LF) and Edema Factor (EF). The titration of specific antibodies in sera of vaccinated animals is crucial to evaluate the efficacy of the vaccination and to obtain epidemiological information for an effective anthrax surveillance. In this study, we developed a Sterne-based Complement Fixation Test to detect specific antibodies induced in animals vaccinated with Sterne 34F2 . We assessed its efficacy in laboratory animals and under field conditions by monitoring the humoral response induced by vaccination in cattle. The results indicated that the Sterne-based CFT is able to identify vaccinated animals with a good sensitivity and specificity offering many benefits especially with regard to costs, standardization and reproducibility of the assay procedure.